A Bifunctional Photo‐Assisted Li–O2 Battery Based on a Hierarchical Heterostructured Cathode. Issue 34 (15th July 2020) - Li, Malin; Wang, Xiaoxue; Li, Fei; Zheng, Lijun; Xu, Jijing; Yu, Jihong
Abstract: Photo‐assisted charging is considered an effective approach to reducing the overpotential in lithium–oxygen (Li–O2 ) batteries. However, the utilization of photoenergy during the discharge process in a Li–O2 system has been rarely reported, and the functional mechanism of such a process remains unclear. Herein, a novel bifunctional photo‐assisted Li–O2 system is established by employing a hierarchical TiO2 –Fe2 O3 heterojunction, in which the photo‐generated electrons and holes play key roles in reducing the overpotential in the discharging and charging processes, respectively. Moreover, the morphology of the discharge product (Li2 O2 ) can be modified via the dense surface electrons of the cathode under illumination, resulting in promoted decomposition kinetics of Li2 O2 during the charging progress. Accordingly, the output and input energies of the battery can be tuned by illumination, giving an ultralow overpotential of 0.19 V between the charge and discharge plateaus with excellent cyclic stability (retaining a round‐trip efficiency of ≈86% after 100 cycles). The investigation of the bifunctional photo‐assisted process presented here provides significant insight into the mechanism of the photo‐assisted Li–O2 battery and addresses the overpotential bottleneck in this system. Abstract : A bifunctional photo‐assisted Li–O2 system is established by employing a hierarchical TiO2 –Fe2 O3 heterojunction cathode. Photoexcited electrons participate in the oxygen reduction reaction process, and the morphology of the discharge products can be tuned for facile oxygen evolution reaction kinetics. Thus, an ultralow overpotential of 0.19 V between discharge and charge plateau with excellent cyclic stability is achieved.